Female Roles in La Cinta Dorada by María Manuela Reina and Models of the World - Aguilar López, Ana María; Miguel Borge, Marta (Lesya Ukrainka Volyn National University, 2021)
Our model of the world that we perceive within ourselves, our conscience, in short, our psychological balance is influenced by our surroundings. Part of the input to which we are exposed in this immediate environment is related to texts, self-managed discourse, which can also influence our internal model of the world; hence they are deserving of our attention. In the same way as the models of the world that we construct throughout our lives, reality is not static and also changes as time goes by. From a social point of view, we can see that the roles of women in modern-day society and the ways that those roles can be perceived today are a consequence of changes initiated in the past within different areas and in a prolonged process over time up until our day. With the aim of evaluating whether female drama has contributed to that change, we present an analysis in this paper of the play La Cinta Dorada [The Golden Ribbon] by María Manuela Reina, written and set in the 1980s, a decade that for Spain implied a more obvious abandonment of the most traditional conceptions of the role of women. In the analysis of the play, we see how the models of the world of the older people are counterposed with those of the younger people, a generational divide that is enriched with the gender difference, as we also analyze how the psychological structures of the female and male characters confront the clichés pertaining to another era in reference to such topics as success, infidelity, matrimony, and gender. The results of our analysis demonstrate how Reina responds to archaic conceptions, thereby inciting the audiences of the day to question their respective models of the world, especially, with regard to the role of the woman in society.
Keywords: psychology of language; psychology of language; model of the world; Spanish dramaturgy; María Manuela Reina; female character; La cinta dorada